純祖 前半期 親鞫·推鞫의 政治性 - 『親鞫日記』·『推案及鞫案』 사례 비교를 중심으로 - 김정자(Kim, Jeong-ja) (법사학연구, 2021)
조선시대 국가와 국왕에 대한 중대한 범죄가 일어나면 국왕이 직접 심문하는 親鞫이 시행되었다. 친국 과정 후, 자세한 조사를 위해서 委官을 정해 궁궐 내에서 시행하는 庭鞫과 義禁府에서 시행하는 推鞫으로 진행되었다. 국왕의 친국 과정 없이 추국청 위관에 의한 정국과 추국이 시행되기도 했으며, 綱常과 관계된 삼성추국 등이 시행되었다. 친국은 『친국일기』, 추국은 『추안급국안』·『추국일기』 등의 자료가 남아있다. 순조 4년(1804) 순조 親政 후, 추국이 행해진 ‘권유․이안묵 사건’은 순조 1년(1801) ‘신유옥사’와 관련된 사안이었다. 벽파 세력 내 反안동 김문 세력에 대한 안동 김문 세력과 시파 세력에 의한 정치 공세였다. 순조는 의도적으로 정조 연간의 世臣을 보존하는 성대한 덕과 착한 뜻을 계승하며, ‘권유․이안묵 사건’을 엄히 다스리지 않았다. 순조 5년(1806) ‘김달순 사건’과 순조 6년(1806) ‘병인경화’ 과정에서 ‘권유․이안묵 사건’은 재론되었다. 당시 위관 중에 金觀柱가 추국이 제대로 되지 않게 막았다는 것이었다. 순조 7년(1807)에도 권유를 논척한 일로 귀양 가 있던 ‘이경신 사건’이 재론되었다. ‘임오화변’․‘병신옥사’․‘신유옥사’에 대한 의리를 유지․지속하는 公論은 재확립되었다. 순조가 친국한 순조 8년(1808) ‘이심도 사건’은 조사과정에서 안동 김문 외척 세력이 배후로 언급되었다. 그러나 순조는 사건이 확산되는 것을 막고자, 한달 만에 친국을 끝마쳤다. 순조 9년(1809)에서 순조 11년(1811) 동안 사도세자 추숭 관련 친국․추국 사건이 일어났다. 趙㯳은 경기감영에 投書를 했고, 張夢瑞는 擊錚을 하였으며, 許倫은 포도청에 掛書를 붙였다. 조경은 杖斃했고, 장몽서는 정조 즉위년 ‘丙申獄事’ 때 李德師․趙載翰이 사도세자를 신원하는 상소를 올린 것과 같은 일을 했다고 진술했다. 장몽서와 허륜은 大逆不道로 正刑하였다. 이 당시 순조와 당국자들은 친국과 추국을 통해서 사도세자의 추숭을 주장하는 세력을 懲討하였고, ‘임오화변’․‘병신옥사’․‘신유옥사’의 의리를 유지․계승․재확립시켰다. 순조 18년(1818) 조경 支屬과 장몽서의 일이 停啓되었다. 이로써 조경․장몽서에 대한 啓辭는 더 이상 거론되지 않았다. 또한 박종경을 논척했다가 유배보내졌던 趙得永 등을 처분을 감해주었다. 풍양 조문 趙萬永의 딸을 세자빈으로 삼아 왕실 내 외척은 안동 김문 세력과 풍양 조문 세력으로 재편된다. During the Joseon period, whenever a grave criminal offence was committed against the King and State, the King would personally interrogate the perpetrator, in a practice named ‘Chin’guk(親鞫).’ After that, more detailed interrogation would ensue, by a designated official(委官) inside the palace (a practice called Jeongguk, 庭鞫), along with another interrogation that assumed the form of Chuguk(推鞫), an interrogation conducted by the Euigeum-bu office. These interrogations were sometimes conducted without the King’s Chin’guk to precede them, while another type of Chuguk named “Samseong Chuguk,” related to ethical issues and morality (綱常), was also practiced. All the Chin’guk practices are recorded in various documentary compilations such as Chin’guk Ilgi(親鞫日記), while the Chuguk instances are compiled in Chu’an-geub Gugan(推案及鞫案) and Chu’guk Ilgi. There was an incident nicknamed as the “Gweon Yu․Lee An-Muk incident,” after King Sunjo(純祖) began to govern the country himself in 1804. It was a political incident staged by the Andong Kim house members and factions affiliated with the house, targeting elements inside the Byeokpa faction which were against the Andong Kim house. King Sunjo intentionally declared that he would walk in the footsteps of the late King Jeongjo, who “looked after vassals who served for generations,” and chose not to punish Gweon Yu that hard. Then, the Gweon Yu․Lee An-Muk incident was again put under a microscope in 1806, during the process of the so-called ‘Byeong’in-year’s Change.’ Filed was an accusation that one of the officials in charge, Kim Gwan-ju(金觀柱), tried to close a relevant matter prematurely, with the intention of protecting the offender. And in 1807, the Case of Yi Gyeong-shin, who was exiled earlier for criticizing Gweon Yu, became the subject of review. 1808, King Sunjo interrogated the ‘Yi Shim-do case’ himself. In the process, the Andong Kim house as an in-law faction was named as the culprit behind the case. Yet King Sunjo needed to contain consequences of the matter, so he completed his personal interrogation within a month. Between 1809 and 1811, there were interrogations conducted either by the King or the vassals, concerning the issue of commemorating the late Crown prince Sado. Jo Gyeong(趙㯳) filed a letter of grievance to the Gyeonggi Gam’yeong office, and Jang Mong-seo(張夢瑞) filed an official Gyeokjaeng(擊錚) complaint, while Heo Ryun(許倫) attached a hand-written poster(掛書) on the wall of the Podo-cheong office(Office of Anti-Burglary). Jo Gyeong was beaten to death(杖斃) during interrogation, while Jang Mong-seo and Heo Ryun, of which the former commented on Yi Deok-sa(李德師) and Jo Jae-han(趙載翰)’s actions as apparently demanding reinstatement of Sado’s honor during the Byeongshin-year Conviction(丙申獄事), were punished under the charge of ‘Ultimate treason(大逆不道),’ and gravely crossing the King. At the time, King Sunjo and the officials in charge have been punishing factions which continued to argue in favor of reinstating Crown prince Sado’s honor since the days of the late King Jeongjo, through a series of Chin’guk and Chuguk interrogations. By doing so the King and others publicly condoned, inherited and reinforced the causes of the Prince Sado’s Tragic Death [lm’o-hwa’byeon], the Byeongshin-year Conviction and the Shinyu-year Purge. In 1818 no more appeals to be submitted to the King regarding issues related to either Jo Gyeong or Jang Mong-seo. As a result, appeals(啓辭) on these issues stopped. Also Jo Deug-yeong(趙得永), who had been exiled after criticizing Park Jong-gyeong, was released. And then, after the daughter of Jo Man-yeong(趙萬永) of the Pung’yang Jo house was named as the new wife of the Crown prince, Andong Kim house and the Pung’yang Jo house came to exist as the two major in-law factions with... KCI Citation Count: 0